Yin-Cold or Yang-Heat Syndrome Type of Traditional Chinese Medicine Was Associated with the Epidermal Growth Factor Receptor Gene Status in Non-Small Cell Lung Cancer Patients: Confirmation of a TCM Concept. (22nd January 2017) - Zhu, Yan-juan; Zhang, Hai-bo; Liu, Li-rong; Liu, Yi-hong; Zhang, Fu-li; Bai, Jian-ping; Li, Yong; Qu, Yan-chun; Qu, Xin; Chen, Xian; Li, Yan; Luo, Shu-yi; et al.
Abstract : Traditional Chinese Medicine (TCM) therapies should be tailored according to the different syndrome types. In order to identify the relationship between the TCM Yin-cold (YC) or Yang-heat (YH) syndrome types and the EGFR gene status, we prospectively studied 310 NSCLC patients. TCM YH or YC was diagnosed by three TCM experts. TCM symptoms and signs were entered into a binary cluster analysis. The relationships between the EGFR gene status, YH or YC syndrome types, and classification by cluster analysis were analyzed using the chi-square test and multivariate logistic regression. In the 299 patients who had their EGFR gene tested, 45.24% YC (76/168) and 25.95% YH (34/131) patients had EGFR mutations ( p = 0.001 ) . Among the 292 patients entered into the cluster analysis, 132 were classified into group A, with signs and symptoms similar to YC, whereas 160 group B patients were similar to YH . In the 281 patients with EGFR tested, 45.67% group A (58/127) and 28.57% group B patients (44/154) had EGFR mutations ( p = 0.003 ) . The EGFR status was independently correlated with TCM syndrome type and classification by cluster analysis on multivariate logistic regression. NSCLC patients with YC were more likely to have EGFR gene mutations.